Analisis Hasil Belajar Menembak dalam Permainan Bola Basket melalui Metode Pembelajaran Imajiner pada Siswa Kelas VII SMPN 5 Lumajang - Alya Dwi Candra Hikaya; Muhammad Nidomuddin; Hari Pamungkas; Havid Yusuf (MAN Insan Cendekia Jambi, 2026)
The purpose of physical education is to develop students in various aspects, including habituation of healthy lifestyle, physical fitness, motor skills, moral and social actions, and emotional development. However, in the learning process, many teachers still emphasize repetitive movement exercises. This monotonous learning method can cause boredom and reduce student interest and participation in participating in learning. The purpose of this study was to determine the improvement of shooting learning outcomes in basketball games through imaginary learning methods in class VII students of SMPN 5 Lumajang. The researcher used classroom action research with 2 cycles, cycle I and cycle II. There are three stages in cycle I, namely; design, activities and observations, and reflection. The study was conducted at SMP Negeri 5 Lumajang in the 2025/2026 academic year, class VII E totaling 30 students. Data obtained in the form of learning outcome tests and observation sheets. From the analysis results, it was found that student learning achievement increased from before the cycle, cycle I, and cycle II, namely, before the cycle (6.67%), cycle I (43.33%), and cycle II (83.33%) meaning that between before PTK and cycle I there was an increase in the percentage of completeness of 36.66% and between cycle I and cycle II there was an increase in the percentage of completeness of 40.00% for the domain of learning outcomes. The results of the study showed that the Imaginary Learning Method can improve the learning outcomes of basketball shooting for class VII E students of SMP Negeri 5 Lumajang in the 2025/2026 Academic Year and the Imaginary Learning Method can be used as an alternative in learning physical education.